A Novel Method to Fabricate Nitrogen and Oxygen Co‐Doped Flexible Cotton‐Based Electrode for Wearable Supercapacitors. Issue 15 (13th August 2019) - Sun, Chao; Zhao, Jing; Guo, Zhiguang; Zhao, Yaping; Cai, Zaisheng; Ge, Fengyan
Abstract: In this work, we prepared a nitrogen and oxygen co‐doped flexible cotton‐based carbon electrode with high electrochemical performance by using a simple dyeing and carbonization method for its potential application in wearable energy storage devices. The optimized dyed cotton‐based electrode with 10 % o.w.f. (percentage on weigh of fabric) dyeing concentration shows a high areal specific capacitance of 1836±20 mF cm −2 at 2 mA cm −2 in aqueous 6 M KOH, superior cycling lifespan (99.1 % capacitance retention after 5000 cycles), good coulombic efficiency, and high rate property. The outstanding properties can be attributed to the synergistic effect between the double‐layer capacitance (superior conductivity, large surface area, and good wetability) and the extra pseudocapacitance originating from N and O heteroatoms in the dye molecules. More importantly, the symmetric supercapacitor created with CDF‐10 % electrodes exhibits a significant volumetric specific capacitance of 18.2 F cm −3 and energy density of 5.7 mWh cm −3 at a power density of 45.2 mW cm −3, which can power an electronic clock for several minutes. The impressive resulting performance demonstrates that this inexpensive synthetic method, which can be scaled‐up, can be used to create promising materials for wearable electronics. Abstract : Painted electrodes : A nitrogen and oxygen co‐doped flexible cotton‐based carbon electrode with high electrochemical performance is prepared by means of a simple dyeing and carbonization method, to be used in wearable energy storage device. The symmetric supercapacitor created by optimized electrodes exhibits a significant volumetric specific capacitance, superior cycling lifespan, and an excellent energy density.